The regulatory effect of polyvinyl pyrrolidone on the microstructure and catalytic activity of nickel phosphides. (20th July 2017) - Xu, Hanghui; Lu, Shaoxiang; Ren, Lili
Abstract: Phase-controlled and shape-controlled nickel phosphides were synthesized using nickel chloride, nontoxic red phosphorus and polyvinyl pyrrolidone (PVP). The hexagonal Ni2 P and tetragonal Ni12 P5 could be transformed via adjusting the amount of polyvinyl pyrrolidone. Besides, the addition of PVP could regulate the particle size of nickel phosphides, so that the large irregular shaped nickel phosphides turned into homogeneous nanoparticles, which further formed three-dimensional porous structure. And its formation mechanism has also been discussed in this paper. The hydrodechlorination catalytic activities of nickel phosphides were promoted markedly with moderate quantity of PVP. While, excessive PVP would cover the active sites of catalysts and lead the catalytic activity decreased. Highlights: Phase- and shape-controlled nickel phosphides were synthesized using PVP. PVP limits the excessive growth of nickel phosphides particles. The catalytic activities of nickel phosphides were obviously improved.